Rupturas conjugais motivadas pelo alcoolismo: uma aproximação às ações de apoio à família do alcoolista - Nascimento, Rosana Cristina Januário do (2014)
This dissertation has the objective of analyzing the Program of Attention to the Family of an Alcoholic which is located in São Miguel township and indentify its comprisement of coverage of care, its efficiency and accessibility as well. The firsts investigation steps of this research occurred in the Núcleo de Prática Jurídica (NPJ) of the University Cruzeiro do Sul in São Paulo (Unicsul), from the observation of daily demand service of Social Service, when daily wives of alcoholics men seek social legal space to join with divorce actions , one of the reasons for marriage rupture: the alcolism. The methodology used in the research was Action Research . It was also utilized the following research tools: bibliographic research on thematic, documental research about anti drugs politics of National Secretary for Alcohol and Drugs (Senad), systematic review of articles in the database of Scielo, raising social assistance resources, semi-structured interview with the local resources responsible, Group Focus and woman attended testimony by Social Service on NPJ, with demand for advice to divorce of their alcoholic partner. The documental research presents through the legislation about alcohol and drugs, the importance about developing actions of alcoholic family attention. With the systematic review we identified the absence of productions in the area of social services about the thematic family and alcoholism . The social fundraising assistance allowed us to identify the services in the area where the research has been done and the semi-structured interview expanded our comprehension about the daily life of these services. The focus group and individual assistance approached us from experiences of alcoholics wives, revealing us a very contradictory universe. The research conducted us to deep our knowledge about alcoholism and its repercussion in the family